Markets for technology in Europe: Mapping demand and its drivers - Christoph Grimpe; Wolfgang Sofka; Philipp Schulz; Geoffrey Thilo Borchhardt (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2019)
Functioning markets for technology are an important determinant for the type, scope and distribution of innovation activities in an economy. However, markets for technology are often underdeveloped or inefficient. Existing theory attributes such imperfections to the supply side or differences in market designs. We know comparatively little, though, about the structural forces that shape the demand side of markets for technology. In this study, we reason that demand depends on the sectoral pattern of innovation and the distance of a country's industry to the global technological frontier. We explore these dimensions based on longitudinal industry-level data from the Community Innovation Survey. We find that the demand on markets for technology is particularly driven by science-based industries and to a lesser degree by scale-intensive industries. Demand decreases, though, the closer industries are to the technological frontier. These findings highlight sector specific opportunities and constraints for policies promoting markets for technology.
Keywords: L10; O32; O34; 330; markets for technology; demand side; patterns of innovation; sectoral studies